Radiological Approaches to Improve Detection of Delayed Hip Joint Complications in Post-COVID Patients (Eurasian Medical Research Periodical, 2025)
The objective of this study is to improve the diagnostic effectiveness of radiological methods in identifying late-stage post-COVID pathologies of the hip joint. This includes defining specific radiological features and patterns that characterize these complications, thereby aiding in early detection, accurate staging, and appropriate management of postCOVID hip joint diseases. Timely and precise diagnosis is essential to prevent progression to severe joint damage and reduce the risk of disability.